Globalization and openness: Lessons from the recent crisis in Southeast Asia - Suthiphand Chirathivat; S. Mansoob Murshed (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Up until the recent crisis, the Southeast Asian region had been regarded as one of the most dynamic regions in the global economy. Their industrial structures have undergone a process of adjustment into more capital-intensive and technologically sophisticated manufacturing sectors. These adjustments created intra-regional flows of foreign direct investment (FDI) followed by the expansion of capital and intermediate goods intrafirm and intra-industry trade among regional economies. The paper argues that globalization and openness are not entirely responsible for the recent Asian crisis. It can be argued, however, that financial and capital-account liberalization was too rapid because domestic institutional capacities were inadequate and unable to cope with the influx of capital. The broader issues raised by the experience of Southeast Asia pertain to lessons for other countries, and this in turn centres on the fundamental question: has globalization and liberalization gone too far?
Keywords: G29; O11; O16; O53; 330; East-Asian crisis; globalization; lessons for other LDCs; Wirtschaftswachstum; Außenwirtschaft; Außenhandelsliberalisierung; Kapitalmarktliberalisierung; Wirtschaftskrise; Südostasien; Finanzmarktkrise